Quality and Quantity in Vocabulary Acquisition (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyses the ongoing debate in second language acquisition (SLA) regarding the relative importance of quality versus quantity in vocabulary acquisition. Scholars have long debated whether learners should prioritize gaining a deep, qualitative understanding of vocabulary, focusing on the nuances, context, and usage of words, or whether expanding the size of their vocabulary is more beneficial. By exploring both perspectives, including the arguments put forth by researchers like Nation, Schmitt, and Krashen, the article delves into how both approaches influence language proficiency. It also evaluates research findings from experimental and observational studies that compare the effectiveness of both strategies.